What the ballad knows the ballad genre, memory culture, and German nationalism - Daub, Adrian 1980- (Oxford University Press, 2022)
"The German ballad was an unusual poetic genre: supposedly inspired by a treasure trove of authorless poems that had for centuries circulated among the common people, the ballad attained popularity in the form of deeply ironic poems written by some of Germany's most canonic authors. Supposedly a celebration of the oral culture of the German Volk, the ballad instead circulated through the emerging channels of nineteenth century culture industry: from anthologies and picture books via the exploding market for song settings, from the opera house to the vaudeville stage, the ballad hewed to its medieval pretence while sounding surprisingly modern. This book traces the strange trajectory of this poetic genre from its origins in the late 18th century to its political appropriations in the 20th. Throughout, the ballad and its path across a wide variety of milieus and media told a surprising and contradictory story of the German nation. What The Ballad Knows shows that, even though the ballad arrived in Germany as a literary genre, it very quickly came to make its home in between different genres and even different media - to the point that laypeople were as likely to encounter it in a concert hall, a classroom, an art museum or a choral rehearsal as they were to encounter it in a book. When cultural conservatives in the early 20th century sought to claim the ballad as a straightforward and serious vehicle of German nationalism, they ignored just how complex the ballad's relationship to the nation had been, and what complexities within nationalism the form had managed to highlight through the decades"--
Keywords: Geschichte; Ballade; Deutsch; Ballads, German / History and criticism; National characteristics, German, in literature; Ballads, German; Criticism, interpretation, etc; Literary criticism; Critiques littéraires